Perfectionism in childhood and adolescence a developmental approach - Flett, Gordon L. 1957- (American Psychological Association, 2022)
"Perfectionism is growing more prevalent among young people today, with increasing numbers of children admitting they feel pressure to be, or appear to be, perfect. This book describes perfectionism's mental health costs and effects on achievement, explaining the myriad and often surprising ways children and adolescents exhibit perfectionism in their family, school, and social environments. Most important, the authors suggest clinical interventions to help perfectionistic children regain perspective, and accept their limitations. Authors Gordon L. Flett and Paul L. Hewitt expertly summarize relevant studies, demonstrating that perfectionism is pernicious and requires a complex and multi-faceted approach to prevention and treatment. A clinically-focused section rounds out the book, with concrete steps counselors and educators can take to help build resilience and adaptability"--